2021
DOI: 10.1152/ajpheart.00535.2020
|View full text |Cite
|
Sign up to set email alerts
|

Carvedilol and exercise combination therapy improves systolic but not diastolic function and reduces plasma osteopontin in Col4a3−/− Alport mice

Abstract: There are currently no FDA-approved treatments for heart failure with preserved ejection fraction (HFpEF). Here we compared the effects of exercise with and without α/β-adrenergic blockade with carvedilol in Col4a3-/- Alport mice, a model of the Phenogroup 3 subclass of HFpEF with underlying renal dysfunction. Alport mice were assigned to the following groups: no treatment control (n=29), carvedilol (n=11), voluntary exercise (n=9), combination carvedilol and exercise (n=8). Cardiac function was assessed by ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…The present results support our previous work that implicated cardiorenal factors in the etiology of HFpEF including trends of slightly lower EF in all AS groups [ 28 , 29 ]. Similarly, Neuburg et al [ 49 ] described systolic dysfunction in 10-week-old 129Sv Col4a3 -/- mice and elevated systolic, diastolic and mean BP in both 129Sv and B6 mice.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The present results support our previous work that implicated cardiorenal factors in the etiology of HFpEF including trends of slightly lower EF in all AS groups [ 28 , 29 ]. Similarly, Neuburg et al [ 49 ] described systolic dysfunction in 10-week-old 129Sv Col4a3 -/- mice and elevated systolic, diastolic and mean BP in both 129Sv and B6 mice.…”
Section: Discussionsupporting
confidence: 93%
“…Specific contributions of immune system modulation and transcription factors involved in cell proliferation and survival, such as signal transducer and activator of transcription 3 (STAT3), have also been described [ 13 , 60 ]. Recently, our group reported a Col4a3 -/- mouse model of HFpEF secondary to CKD that implicated osteopontin as an etiological effector and carvediol, an α/β adrenergic antagonist, as therapeutic [ 10 , 28 ]. Despite decades of investigation, an established cure for AS remains elusive, and standard treatment for patients is limited to ACE inhibitors that slow disease progression when applied at an appropriate early stage before onset of ESRF [ 16 , 17 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Lastly, studies investigating combined β-blocker and exercise training suggest improvements in exercise capacity in humans with HF or post myocardial infarction [243,244]. In mice with HF, combined beta-blocker and exercise training therapy (4 weeks) provided additive improvements to cardiovascular function compared with individual therapy through reduced HR (17 vs 16 vs 7%), increased stroke volume (71 vs 25 vs 34%) and increased EF (41 vs 34 vs 13%) in combined vs beta-blocker only vs exercise training only, respectively [245]. In support, another study in mice (5-7 months) with HF found combined therapy improved exercise tolerance, reduced mortality, and improved ventricular contractility [246].…”
Section: Combined Exercise Training and Drug Therapymentioning
confidence: 99%